Shipping Law - Baughen, Simon (Routledge, 2023)
"In this indispensable textbook, Simon Baughen expertly covers the whole spectrum of English shipping law, placing the highly specialised rules of shipping in a commercial context and relating them to the general principles of contract and tort law. The 8th edition is brought fully up to date, covering all the relevant legal implications following on from Brexit. In-depth commentary on judicial decisions and well-balanced coverage and analysis of recent and key cases provide an up-to-date reference for students on Shipping Law courses. All key topics are comprehensively covered, including bills of lading, charterparties, salvage, marine pollution, jurisdiction, choice of law, arbitration, and accidents and collisions. Continuing significant and noteworthy developments in shipping law are explored in this new edition, such as the introduction into the House of Lords in October 2022 of the Electronic Trade Documents Bill. The field of international conventions has also seen several changes since the previous edition. Shipping Law provides an invaluable source of reference, both for students and those in practice. The book's accessible narrative and useful glossary of key terms will especially benefit students new to shipping law or from non-law backgrounds"--